Effects of the Dietary Approaches to Stop Hypertension (DASH) Eating Plan on the Metabolic Side Effects of Corticosteroid Medications. (18th May 2016) - Azadbakht, Leila; Izadi, Vajihe; Ehsani, Simin; Esmaillzadeh, Ahmad
Abstract : Objective : We aimed to determine the effects of the Dietary Approaches to Stop Hypertension (DASH) diet on the metabolic side effects of corticosteroid medication use. Design : A randomized clinical trial was undertaken in 60 patients on corticosteroid therapy for 10 weeks. Patients were randomly assigned to a DASH or control diet. Carbohydrate, protein, and fat in both groups were 50–60%, 15–20%, 30%, respectively. DASH diet was a diet rich in fruits, vegetables, whole grains, low-fat dairy products, and low in total and saturated fat and cholesterol, refined grains, and also sweets. Fasting blood samples were collected to determine blood glucose and lipid profile. Blood pressure and anthropometric measurements were measured based on the standard guidelines. Results : The mean age and body mass index (BMI) were 31.1 ± 3.6 year and 26.9 ± 2.6 kg/m 2, respectively. There were no significant differences between age and BMI in two groups at baseline. No significant difference was observed in body weight and waist circumference following the DASH diet compared to control diet. Systolic and diastolic blood pressures were significantly different following the DASH eating pattern ( P = 0.04). Serum total cholesterol and fasting blood glucose significantly decreased in those following the DASH diet after adjustment for potential confounders. Conclusion : The DASH diet had beneficial effects on several metabolic side effects among patients using corticosteroid medications.